Determinan Kejadian Putus Sekolah di Provinsi Kepulauan Bangka Belitung Tahun 2021 - Resky Amelia; Neli Agustina (Politeknik Statistika STIS, 2022)
The country’s economic growth cannot be separated from quality of human resources (HR) that one of benchmark is level of education. Bangka Belitung is one of the province with dropout rate above the national level. This study aims to analyze the effect of 7-18 year old children demographic socioeconomic characteristics on the school dropouts in the Province of Kepulauan Bangka Belitung in 2021. By applying descriptive analysis, the results obtained a general picture that the number of dropouts in Province of Kepulauan Bangka Belitung in 2021 is increasing along with the increasing level of education. Result of binary logistic regression analysis show that PIP utilization status, household head work status, home ownership status, number of household members, household head education level, and residential area status had a significant effect on dropouts in the Bangka Belitung Islands Province in 2021. The results of this analysis are expected to be the basis for local governments in determining policies and steps to reduce the number of dropouts.